2005
DOI: 10.1038/sj.eye.6701945
|View full text |Cite
|
Sign up to set email alerts
|

Pars plana vitrectomy for diabetic macular oedema: OCT and functional correlations

Abstract: Purpose A prospective study to evaluate the macular structural and functional effects of pars plana vitrectomy (PPV) for persistent diffuse clinically significant macular oedema (CSMO). Method A total of 12 patients with persistent diffuse CSMO were recruited and underwent assessment including best-corrected visual acuity, fundus fluorescein angiography, optical coherence tomography (OCT) and fine matrix mapping (FMM) at baseline and over a period of a year poststandard three-port PPV. Results The median basel… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
26
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 28 publications
(31 reference statements)
0
26
0
Order By: Relevance
“…Earlier studies involving OCT mostly focused on macular edema and a correlation was found between visual acuity (VA) and reduction in central macular thickness [7,8,9,10,11,12]. However, some eyes with DME have a poor visual outcome despite resolution of macular edema after successful treatment [13,14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Earlier studies involving OCT mostly focused on macular edema and a correlation was found between visual acuity (VA) and reduction in central macular thickness [7,8,9,10,11,12]. However, some eyes with DME have a poor visual outcome despite resolution of macular edema after successful treatment [13,14,15,16,17,18].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, vitrectomy has been reported to be beneficial in these situations. Some studies, however, have shown that vitrectomy is effective even when there is no evidence of macular traction [18][19][20][21] . Perhaps this is due to removal of the posterior hyaloid also removes toxic substances, such as histamine, free radical scavengers, and VEGF, which may be harbored in the preretinal space [22] .…”
Section: Vitrectomymentioning
confidence: 99%
“…However, OCT is becoming the mainstay of objective treatment monitoring and follow-up of patients with macular edema. It is widely accepted in trials and studies (DRCRN, 2010;Estabrook et al, 2007;Otani & Kishi, 2000;Patel et al, 2006), as well as in clinical settings.…”
Section: Oct Findings In Dme 31 Retinal Thicknessmentioning
confidence: 99%
“…Macular traction is a factor implemented in the pathogenesis of macular edema and there is increasing evidence that releasing it via vitrectomy may be beneficial (DRCRN, 2010;Patel et al, 2006;Yanyali et al, 2007). Macular traction may be induced by vitreoretinal interface abnormalities such as incomplete posterior vitreous detachment (PVD) or ERM.…”
Section: Vitreoretinal Interface and Macular Tractionmentioning
confidence: 99%